2011
DOI: 10.1189/jlb.0610374
|View full text |Cite
|
Sign up to set email alerts
|

Technical Advance: Langerhans cells derived from a human cell line in a full-thickness skin equivalent undergo allergen-induced maturation and migration

Abstract: In this report, the construction of a functional, immunocompetent, full-thickness skin equivalent (SE) is described, consisting of an epidermal compartment containing keratinocytes, melanocytes, and human LCs derived from the MUTZ-3 cell line (MUTZ-LC) and a fibroblast-populated dermal compartment. The CD1a(+)Langerin(+)HLA-DR(+) MUTZ-LCs populate the entire epidermis at a similar density to that found in native skin. Exposure of the SE to subtoxic concentrations of the allergens NiSO(4) and resorcinol resulte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
72
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 35 publications
(37 reference statements)
5
72
0
1
Order By: Relevance
“…MUTZ-3 LC closely resemble their native counterparts, both phenotypically and functionally (Kosten et al, 2015b;Masterson et al, 2002;Santegoets et al, 2008). Indeed, in the past we have shown in skin equivalents with integrated Langerhans Cells (SE-LC) that upon allergen exposure MUTZ-3 LC mature and migrate in a CXCL12 dependent manner from the epidermis to the dermis, whereas upon irritant exposure MUTZ-3 LC migrate in a CCL5 dependent manner and undergo an IL-10 dependent phenotypic switch into a macrophage-like cell in the dermis, closely mimicking our observations in excised skin (Kosten et al, 2015b;Ouwehand et al, 2008Ouwehand et al, , 2011b). Recently, we described a full thickness oral gingiva equivalent (GE) consisting of a reconstructed epithelium on a fibroblast populated collagen hydrogel (lamina propria) and shown that the GE secretes negligible amounts of key chemokines involved in LC migration in skin (Kosten et al, 2015a).…”
supporting
confidence: 83%
See 2 more Smart Citations
“…MUTZ-3 LC closely resemble their native counterparts, both phenotypically and functionally (Kosten et al, 2015b;Masterson et al, 2002;Santegoets et al, 2008). Indeed, in the past we have shown in skin equivalents with integrated Langerhans Cells (SE-LC) that upon allergen exposure MUTZ-3 LC mature and migrate in a CXCL12 dependent manner from the epidermis to the dermis, whereas upon irritant exposure MUTZ-3 LC migrate in a CCL5 dependent manner and undergo an IL-10 dependent phenotypic switch into a macrophage-like cell in the dermis, closely mimicking our observations in excised skin (Kosten et al, 2015b;Ouwehand et al, 2008Ouwehand et al, , 2011b). Recently, we described a full thickness oral gingiva equivalent (GE) consisting of a reconstructed epithelium on a fibroblast populated collagen hydrogel (lamina propria) and shown that the GE secretes negligible amounts of key chemokines involved in LC migration in skin (Kosten et al, 2015a).…”
supporting
confidence: 83%
“…The number and phenotype of migrated MUTZ-3 LC was determined by flow cytometry in the SE-LC and GE-LC after disrupting the collagen gels with collagenase as described previously (Ouwehand et al, 2011b;Kosten et al, 2015b). Cell staining was performed using mouse anti-human CD1a-PE (IgG1, BD Pharmingen, San Diego, CA, USA).…”
Section: Flow Cytometrymentioning
confidence: 99%
See 1 more Smart Citation
“…4) [42]. Using a full-thickness tissue-engineered skin model containing fully functional MUTZ-3-derived LCs (MUTZ-LC), the MUTZ-LCs were demonstrated to mature and to acquire the ability to migrate towards C-X-C motif ligand (CXCL)12 and C-C motif ligand (CCL)19/21 in a comparable manner with primary LCs in skin explants [43].…”
Section: Important Gapsmentioning
confidence: 99%
“…An immunocompetent skin equivalent model (by Sue Gibbs) the ideal future will have an immunocompetent equivalent model that may replace one-to-one the in vivo method with the construction of a functional, immunocompetent, full thickness skin equivalent model (Ouwehand et al, 2011).…”
Section: Pre-validation Of a Tiered Approach (By Marc Teunis)mentioning
confidence: 99%